Meta-analysis of latent tuberculosis in healthcare workers in Iran: a retrospective review. (3rd February 2021) - Sepehri, NazaninZahra; Saghanezhad, Seyed Mohammad; Khoddami, Farshad; Arasteh, Amin; Delirakbariazar, Marziyeh; Khaledi, Azad
Abstract : Background: Here we review the status of latent tuberculosis (LTB) in Iranian healthcare workers (HCWs). Methods: A literature search was conducted using keywords according to the Preferred Reporting Items for Systematic Review and Meta-Analyses instructions. Cross-sectional studies published from 1 January 2000 through 1 January 2019 were retrieved. Meta-analysis was performed using Comprehensive Meta-Analysis software using the random effects model, Cochran's Q and I 2 tests. Publication bias was estimated by funnel plot and Egger's linear regression test. Results: Among 774 articles retrieved in the primary literature search, 21 studies met the eligibility criteria. No publication bias was observed among the included studies (p=0.07). The prevalence of LTB ranged from 7% to 63% in Iranian HCWs from different geographical areas. The overall combined prevalence of LTB among Iranian HCWs was 30.9% (95% confidence interval 24.2 to 38.5). Also, 52.4% of the included studies showed a significant correlation between occupation and LTB incidence (p<0.05). Conclusions: The prevalence of LTB was high among Iranian HCWs. This requires developing comprehensive information databases and surveillance systems for detecting LTB among HCWs. It is also essential to periodically screen for LTB in HCWs to provide a timely diagnosis of the infection. It is recommended to perform a tuberculin skin test, a useful tool for screening and treatment of LTB, on an annual basis in HCWs.